Potrzeby żywnościowe a rozwój agrokompleksu i rynku rolnego w Polsce - Babiak, Jerzy (Wydział Prawa i Administracji UAM, 1972)
The author comes to the conclusion that 1) organizational improvement of the activities of the institutions purchasing agricultural products, 2) modernization of the technical base of the purchasing apparatus, 3) creation of a transport base for direct collecting of farm produce, 4) preparation of an organizational model in the sphere of transportation services for farmers (delivery of production means and direct collection of farm produce), 5) rise in expenditure for food processing industries, 6) extension of supply contracts and agreements running for many years, are essential to supply the necessary quantity of foodstuffs, i. e. to secure a balanced growth in all the fields that take part in food production.
Food Requirements and Agricomplex Development in Poland